2016
DOI: 10.5194/isprs-archives-xli-b2-71-2016
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Processing of Big Point Clouds Using Z-Order-Based Partitioning

Abstract: ABSTRACT:As laser scanning technology improves and costs are coming down, the amount of point cloud data being generated can be prohibitively difficult and expensive to process on a single machine. This data explosion is not only limited to point cloud data. Voluminous amounts of high-dimensionality and quickly accumulating data, collectively known as Big Data, such as those generated by social media, Internet of Things devices and commercial transactions, are becoming more prevalent as well. New computing par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The experimental results showed that Apache Spark had a better performance than traditional DBMSs for various types of geospatial queries [26]. The methods based on Apache Spark for large point cloud management are described in [29,30]. The method for ingesting the point clouds in the Apache Spark data structures is presented in [29].…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that Apache Spark had a better performance than traditional DBMSs for various types of geospatial queries [26]. The methods based on Apache Spark for large point cloud management are described in [29,30]. The method for ingesting the point clouds in the Apache Spark data structures is presented in [29].…”
Section: (A)mentioning
confidence: 99%
“…The method for ingesting the point clouds in the Apache Spark data structures is presented in [29]. The indexing of point clouds based on space filling curves is presented in [30]. The methods for classification, feature identification, and change detection using large point clouds are described in [26,27,29,31,32].…”
Section: (A)mentioning
confidence: 99%
“…In addition, Spark provides a richer interface so that applications need not follow the rigid structure of one map and one reduce function as per the original MapReduce framework. The use of Spark for LiDAR point cloud analysis is seen in various research (e.g., [16,18,[37][38][39][40]). In all of those cases, parallel computing was used for post-acquisition data analysis.…”
Section: Parallel Computing For Lidar Data Analysismentioning
confidence: 99%
“…We have already shown the successful use of cloud based machine learning for point cloud classification (Liu and Boehm, 2015). While the established tools do not typically provide spatial functionality such as indexing an query, these can be implemented on top of existing frameworks (Alis et al, 2016).…”
Section: Concuisons and Outlookmentioning
confidence: 99%